Reaction of Zinc Proteome with Biologically Important Metal Binding Ligands - (:unkn) unknown (My University, 2015)
Fluorescent sensors have been widely used as microscopic tools to image Zn2+ on a cellular level. Recently, it has been established that the sensors TSQ and Zinquin form adducts with Zn-proteins and image fractions of the Zn-proteome.1 Since TSQ and Zinquin bind specifically to many Zn-proteins, it is hypothesized that other metal binding ligands, both synthetic and natural, may also bind to the Zn-proteome. Biologically active 1,10-phenanthroline (Phen) and related molecules were investigated for their ability to bind to Zn-proteome. Similarly, the cellular tripeptide, glutathione was investigated. It was observed that Phen and some other metal binding, bidentate ligands, were able to displace TSQ from the TSQ-Zn-proteome. Specifically when cellular Zn-proteome reacted with TSQ, adduct formation occurs, that was detected by fluorescence emission at 470 nm. Upon reaction of TSQ-Zn-proteome with 1,10-phenanthroline, glutathione, and some other related small molecules, a significant decrease in fluorescence was observed, indicating the displacement of TSQ by each competing ligand. Native SDS (NDS) PAGE electrophoresis of the product of the reaction of 1,10-Phenanthroline with TSQ-Zn-proteome further confirmed the displacement of TSQ from an array of Zn-proteins. This reaction was further characterized with the use of Zn-alcohol dehydrogenase as a model enzyme that reacts with TSQ and Phen. These studies reveal the Zn-proteome as widely available for adduct formation at its zinc binding sites. The importance of such reactions is being investigated.